Perspectives of public health laboratories in emerging infectious diseases - Kaw Bing Chua; Duane J Gubler (Emerging Microbes and Infections)
The world has experienced an increased incidence and transboundary spread of emerging infectious diseases over the last four decades. We divided emerging infectious diseases into four categories, with subcategories in categories 1 and 4. The categorization was based on the nature and characteristics of pathogens or infectious agents causing the emerging infections, which are directly related to the mechanisms and patterns of infectious disease emergence. The factors or combinations of factors contributing to the emergence of these pathogens vary within each category. We also classified public health laboratories into three types based on function, namely, research, reference and analytical diagnostic laboratories, with the last category being subclassified into primary (community-based) public health and clinical (medical) analytical diagnostic laboratories. The frontline/leading and/or supportive roles to be adopted by each type of public health laboratory for optimal performance to establish the correct etiological agents causing the diseases or outbreaks vary with respect to each category of emerging infectious diseases. We emphasize the need, especially for an outbreak investigation, to establish a harmonized and coordinated national public health laboratory system that integrates different categories of public health laboratories within a country and that is closely linked to the national public health delivery system and regional and international high-end laboratories.